(untitled) (Research, Society and Development, 2019)
This article aims to socialize the results of a scientific research denominated: Conceptions about evaluation of the learning of teachers who work in High School at the Federal Institute of Education Science and Technology of Mato Grosso - IFMT, Campus São Vicente. The relevance of the topic is presumed because, the school evaluation impacts on the process of teaching learning, being the means to define the success or failure of the student. It is recommended that in the conceptions about evaluation of learning or school evaluation, two logics are evidenced: Classification Evaluation and Formative Evaluation. This paper presents a contextualization of this duality and situates the object of this research in relation to the theoretical background on learning evaluation Allal (1986), Villas Boas (2014), Luckesi (2002, 2011) Hoffmann (2014), Perrenoud (1998) and Vasconcellos (2007). The scientific research involved qualitative research studies with emphasis on triangulation for data production, assuming an interpretive character of categorization of these data in front of the scenario and panorama of the crazy institution of this study. We chose interviews with the teachers, for which we used a script that guided the dialogue. We also investigated 25 students enrolled in the third year of high school. The issues raised here contributed to a clearer diagnosis of the factors that demonstrate the success of the teaching-learning process, as well as to broaden the debate about how to guarantee the right to learning and the maintenance of physical and human resources, guaranteeing an efficient and transformative education.